Response surface for screw dislocation: Twin boundary interactions in FCC metals. (15th August 2020) - Rao, Satish I.; Dupraz, Maxime; Woodward, C.; Parthasarathy, T.A.
Abstract: In a previous manuscript, large scale 3D atomistic simulations were used to study the interaction between a curved dislocation with a dominant screw character and a Coherent Twin Boundary (CTB) for three FCC metals (Al, Cu and Ni) using 6 embedded-atom method (EAM) potentials [1] . Under both uniaxial and multiaxial stresses, both transmission mechanism and critical transmission stress differ from the results reported in 2D simulations [1] . Transmission mechanisms were found to be material dependent, and non-glide (Escaig) stresses have a profound effect on the transmission. In order to provide input for constitutive equations for mesoscopic approaches, the previous results are used to inform analytic models that incorporates mechanisms observed in the atomistic simulations [1] . For Al, the Fleischer mechanism of cross-slip at the twin boundary [2] is used whereas for Cu and Ni, Escaig mechanism of cross-slip [3] at the twin boundary is invoked. For Cu and Ni the transmission stress is determined by the critical stress required to grow the cross-slip nucleus in the adjacent grain, as opposed to growth of cross-slip nucleus in the twin boundary. As a result, the critical transmission stress in these materials is almost athermal. The analytic, mechanistic model reproduces the atomistic simulation results for the Escaig stress dependence of the transmission stress as well as its dependence on a shear component in the CTB fairly well, within 10% for the Escaig stress dependence. Graphical abstract: Fig. (a, adapted from [1] ): Evolution of the critical transmission stress, σrss_trans as a function of the Escaig stress, σEscaig in Al, Cu and Ni. The load ratios, which is the ratio of σyy to σzz, are specified for the circled points. Here, x is along [1 1 1], y along [-2 1 1] and z along [0 -1 1] in the initial grain (γ  glide plane). In the adjacent twinned grain (γ' glide plane), x is along [1 1 1], y along [2 -1 -1] and z along [01 -1]. Model results for simulations in FCC Cu (b) and FCC Ni (c): Critical cross-slip nucleation stresses (MD and experimental strain rates) for cross-slip nucleation in the twinned grain, critical cross-slip nucleus growth stresses for growth in the twinned grain and critical transmission stresses for screw dislocations moving into the adjacent twinned grain from the model presented in the manuscript for Cu, Ni. Also shown in (b) are the cross-slip nucleation and growth stresses for the experimental conditions of [6] . Image, graphical abstract